Strategy to Suppress Corruption and Money Laundering in the Digital Age - Redentor Goncalinho Antonio Obe; Florianus Aloysius Nay (Journal of Digital Law and Policy, 2022)
The purpose of this research is to describe and understand the criminal sentencing model for corrupt acts accompanied by money laundering crimes. This research uses a qualitative approach with a normative legal design. Data collection techniques include literature review, and data analysis techniques include presentation, reduction of data, and collection and verification. The research results showed that the sentencing for corrupt acts accompanied by money laundering is not the same as for money laundering with an underlying corruption crime, which would impose penalties according to Article 3 of Law No. 8 of 2010 on the eradication of money laundering. Specifically, in the case of corrupt acts accompanied by money laundering, which applies an absorption system, in line with the teachings of Article 65 of the Indonesian Criminal Code. The conclusion of this research is that the doctrine of Concursus from the Chamber of Criminal Matters of the Supreme Court of the Republic of Indonesia Tangerang has a legal foundation that serves as a guide or sentencing basis, which can be revised regarding the sentencing model that should be applied for corrupt acts accompanied by money laundering crimes. Preserving the integrity of digital transactions in order to prevent the risk of money laundering. Effective measures must be taken to ensure that digital transactions are secure and that any illegal activities are detected and punished accordingly.